Dignity Therapy for End-of-Life Care Patients: A Literature Review. (23rd February 2021) - Cuevas, Pearl Ed; Davidson, Patricia; Mejilla, Joylyn; Rodney, Tamar
Dignity therapy as an intervention has been used for individuals receiving palliative care. The goal of this review is to explore the current state of empirical support to its use for end-of-life care patients. Data sources were articles extracted from search engines PubMed, Cochrane, Embase, CINAHL, Web of Science, and PsycINFO. The years searched were 2009 to 2019 (10-year period). The review process was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Results revealed the feasibility, acceptability, satisfaction, and effectiveness of dignity therapy for life-limiting cases/conditions of patients in different age groups. It also highlighted the importance of the therapy setting and the need to apply this in the cultural context. The meaning of dignity therapy to patients and their family care members also emerged. Findings showed most patients displayed the need to leave a legacy and from this their core values surfaced. In conclusion, this review highlighted the contribution of dignity therapy to the holistic care of patients who hope to leave a legacy. The therapy was also relevant to decrease the anxiety; depression, and burden of family members throughout the palliative care period of their loved ones.